Pemanfaatan Model Pembelajaran Kooperatif Tipe Make A Match Terhadap Hasil Belajar Matematika Melalui Materi Bangun Datar - Putri Handayani; Jonata (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2021)
In this article, the researcher takes one of the focus parts of the second problem formulation from the research thesis work which is about student learning outcomes. Mathematics education in education is given to all levels, starting from early childhood education, elementary school education, junior high school level, high school level, even to the state tertiary level. Because mathematics education is one of the foundations of science technology capabilities, while teachers do not care about students about understanding students thinking skills in learning mathematics. 3rd grade students at SD Negeri Cipocok Jaya 4 who were the subjects in this study. Class action research is the method used in this study and the approach used is a qualitative approach. Researchers conduct interviews on student learning outcomes. Transcript results from homeroom teacher and third grade students after being given action during mathematics learning using the make a match learning model on flat waking material that the learning model with given media cards in the form of questions and answers can facilitate students in learning mathematics, so that by matching cards can delight students in learning and students are not bored in learning, unsaturated, not sleepy, and many do not complain about the material given and students are very enthusiastic in learning. The seventy-five percent indicator is successful, and a researcher is deeply moved by the action through that model. With that, it can be concluded that the use of learning models make a match in mathematics learning can improve student learning outcomes in flat-up material.